Mitigation of biofouling with co-deposition of polydopamine and curcumin on the surface of a thin-film composite membrane. (January 2023) - Park, Chansoo; Lei, Ji; Kim, Jong-Oh
Abstract: Reverse osmosis (RO) membrane has been widely used in various water treatment fields as an efficient desalination technology, but serious biofouling problem arises in the actual application process. Curcumin is known as a natural compound that can reduce biofouling by inhibiting the growth of microorganisms based on quorum sensing. Dopamine, a molecule with excellent adhesion and functionalization on the material's surface, has high research value for applying a curcumin coating to the membrane surface. Curcumin degrades under alkaline conditions, whereas dopamine must polymerize under alkaline conditions. Simultaneously, a coating may adversely affect curcumin. Therefore, a two-step coating process was considered by self-polymerizing dopamine on the thin-film composite membrane surface and then dip-coating curcumin attached to the polydopamine layer. Furthermore, the effect of time and concentration on the surface modification before and after membrane modification was investigated. The highest permeability of 1.39 L/m 2 /hr/bar was achieved with the modified membranes. The number of gram-positive bacteria decreased from 6.71 × 10 6 to 9.67 × 10 5  CFU/mL. This result is meaningful for antifouling through modification of the membrane surface. Use of curcumin can be applied to reduce biofouling and extend the lifetime of the membrane without pretreatment or membrane cleaning. Graphical abstract: Image 1 Highlights: Coating of membrane may possess short-term effects and toxicity in the environment. Curcumin is a natural compound that inhibits biofouling with co-deposition of dopamine. Various concentrations of coating were applied on the surface of the membrane. Surface of the modified membranes and anti-bacterial effect were analyzed. Modified membranes showed up to 99.8% decrease in bacterial growth.